1996
DOI: 10.1074/jbc.271.14.8488
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mitogen-activated Protein (MAP) Kinase-activated Protein Kinase-3, a Novel Substrate of CSBP p38 MAP Kinase

Abstract: CSBP p38 is a mitogen-activated protein kinase that is activated in response to stress, endotoxin, interleukin 1, and tumor necrosis factor. Using a catalytically inactive mutant (D168A) of human CSBP2 as the bait in a yeast two-hybrid screen, we have identified and cloned a novel kinase which shares approximately 70% amino acid identity to mitogen-activated protein kinase-activated protein kinase (MAPKAP kinase)-2, and thus was designated MAPKAP kinase-3. The binding of CSBP to MAPKAP kinase-3 was confirmed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
239
0
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 331 publications
(248 citation statements)
references
References 33 publications
5
239
0
3
Order By: Relevance
“…4). The activation of an epitope-tagged version of MAPKAP-K3 by TNF or osmotic shock and blockade of its activation by SB 203580 has been demonstrated previously after its transfection into HeLa cells [18]. However, by raising antibodies that immunoprecipitate either MAPKAP-K2 or MAPKAP-K3, we have been able to study the activation of the endogenous enzymes in the same cell lysates.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…4). The activation of an epitope-tagged version of MAPKAP-K3 by TNF or osmotic shock and blockade of its activation by SB 203580 has been demonstrated previously after its transfection into HeLa cells [18]. However, by raising antibodies that immunoprecipitate either MAPKAP-K2 or MAPKAP-K3, we have been able to study the activation of the endogenous enzymes in the same cell lysates.…”
Section: Discussionmentioning
confidence: 75%
“…MAPKAP-K2 purified from rabbit skeletal muscle was provided by [18]) was induced with 30 ~tM isopropyl-13-D-thiogalactoside for 20 h at 22°C. The glutathione-S-transferase (GST)-MAPKAP-K3 fusion protein was purified by affinity chromatography on glutathione-Sepharose (Sigma) and showed two bands migrating on SDS/polyacrylamide gels with apparent molecular masses of 67 and 65 kDa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first p38α substrate identified was the MAP kinase-activated protein kinase 2 (MAPKAPK2 or MK2) [1,15,52]. This substrate, along with its closely related family member MK3 (3pk), were both shown to activate various substrates including small heat shock protein 27 (HSP27) [53], lymphocyte-specific protein 1 (LSP1) [54], cAMP response element-binding protein (CREB) [55], transcription factor ATF1 [55], SRF [56], and tyrosine hydroxylase [57].…”
Section: Downstream Substrates Of P38 Group Map Kinases Protein Kinasmentioning
confidence: 99%
“…p38a Mitogen-activated protein kinase (MAPK)-deficient [Rousseau et al, 2006] and MAP kinase-activated protein kinase 2 (MK2)-deficient fibroblasts showed reduced ability to migrate in scratch wound assays [Liu et al, 2007]. Apart from MK2, mammalian cells harbor a related p38-regulated protein kinase designated MK3 or 3pK [McLaughlin et al, 1996, Sithanandam et al, 1996. MK2 and MK3 show 75 % overall sequence identity on the amino acid level with the highest similarity within the catalytic domain and lower conservation in the N-terminal region [Gaestel, 2006], which displays a clear proline-rich motif in MK2 but not in MK3.…”
Section: Introductionmentioning
confidence: 99%